Shoulder pain in female wheelchair basketball players - Curtis, K. A.; Black, K. (Journal of Orthopaedic & Sports Physical Therapy, 1999)
Abstract: Study Design: Descriptive self-report survey. Objectives: To assess activity level, medical history, and the prevalence and intensity of shoulder and upper extremity pain experienced during functional activities in female athletes who compete in wheelchairs. Background: Previous studies have documented a high incidence of upper extremity soft tissue disorders in athletes who compete in wheelchairs. None of these studies have specifically focused on female athletes who use wheelchairs. Methods and Measures: Forty-six female wheelchair basketball players completed an anonymous survey that included demographic data, medical history data, and the Wheelchair User`s Shoulder Pain Index (WUSPI). The WUSPI is a valid and reliable self-report measure scored from 0 to 150, with higher scores indicating a greater intensity of shoulder pain during functional activities. Results: The average age of the respondents was 33.2 (± 9.1) years, with an average of 12.5 (± 10.2) years of wheelchair use. Their disabilities included 39% spinal cord injury, 28% various lower extremity musculoskeletal and neuromuscular disabilities, 13% postpolio paralysis, 11% spina bifida, and 9% amputations. Only 14% of the subjects reported shoulder pain prior to wheelchair use. In contrast, 72% of the subjects reported shoulder pain since wheelchair use, with 52% reporting current shoulder pain. Overall, the subjects scored an average ± SD performance-corrected total WUSPI score of 15.6 ± 20.5 on a scale of 0 to 150 points, with 0 representing no pain. The highest intensity of shoulder pain was reported during household chores, propulsion on ramps or inclines, lifting overhead, and while sleeping. Conclusions: Shoulder and upper extremity pain was a very common problem reported by over 90% of the subjects in this study. Prevention of pain and chronic disability in athletes who use wheelchairs should be addressed by coaches, players, and health care professionals.